Common intestinal parasitic infections in an improved water access, sanitation, and hygiene profile setting in North Jakarta, Indonesia - Narayani, Dewa AJ.; Ali, Soegianto; Surja, Sem S.; Kristin, Helen; Hangestu, Anastasia; Widowati, Tria A.; Wijaya, Meiliyana; Kaisar, Maria MM. (Narra Sains Indonesia, 2024)
Intestinal parasitic infections (IPIs), caused by helminths and/or protozoa, continue to be a significant public health concern in Indonesia. Water access, sanitation, and hygiene practices (WASH) are influential factors for IPIs, especially among children. The aim of this study was to investigate the association between WASH and IPIs among school-aged children. A cross-sectional study involving 338 school-age children in an urban slum area in North Jakarta, Indonesia, was conducted using stool specimens subjected to microscopic and real-time polymerase chain reaction (rt-PCR) examination. The children underwent a finger-prick blood test and anthropometric measurements to determine anemia and nutritional status. Parents whose children participated in stool and blood examinations were interviewed using a modified WASH questionnaire. Helminth infections were not found in this study, whereas the overall prevalence of intestinal protozoa parasitic infection (IPPI) was 18.3% and 52.4% by microscopy and rt-PCR, respectively. Blastocystis spp. was found to have the highest prevalence (microscopy: 12%; rt-PCR: 48.6%), followed by Giardia intestinalis (microscopy: 0.6%; rt-PCR: 6.7%), Cryptosporidium spp. (microscopy: 5.1%; rt-PCR: 1.6%), and Entamoeba histolytica/dispar (microscopy: 0.6%; rt-PCR: 3.2%). Additionally, Dientamoeba fragilis was detected by rt-PCR at 4.1%. Furthermore, the discrepancies between microscopy and rt-PCR were observed in 8.9% (n=28) of the examined specimens. The majority of the respondents had a low-risk category of WASH profile. School children aged 5–10 years old (OR=2.06; 95%CI=1.27–3.33) and those who drank unprocessed cooking water (OR=1.95; 95%CI=1.07–3.57) were significantly associated with IPPI. The present study demonstrated that rt-PCR provides a better understanding of IPI epidemiology and has potential as a monitoring strategy for managing IPIs. Even though this population exhibits an adequate WASH profile and is not directly associated with IPIs, conducting a more in-depth observation of WASH facilities and practices is recommended to ensure a comprehensive assessment of the WASH profile. Additionally, engaging stakeholders in health promotion programs to ensure the sustainability of a good WASH profile and awareness of parasitic infections will be advantageous in achieving optimal urban health.